The role of Fas-associated phosphatase 1 in leukemia stem cell persistence during tyrosine kinase inhibitor treatment of chronic myeloid leukemia - Huang, W; Luan, C-H; Hjort, E E; Bei, L; Mishra, R; Sakamoto, K M; Platanias, L C; Eklund, E A (Leukemia, 2016)
Chronic myeloid leukemia (CML) is characterized by expression of Bcr-abl, a tyrosine kinase oncogene. Clinical outcomes in CML were revolutionized by development of Bcr-abl-targeted tyrosine kinase inhibitors (TKIs), but CML is not cured by these agents. CML leukemia stem cells (LSCs) are relatively TKI insensitive and persist even in remission. LSC persistence results in relapse upon TKI discontinuation, or drug resistance or blast crisis (BC) during prolonged treatment. We hypothesize that increased expression of Fas-associated phosphatase 1 (Fap1) in CML contributes to LSC persistence and BC. As Fap1 substrates include Fas and glycogen synthase kinase-3β (Gsk3β), increased Fap1 activity in CML is anticipated to induce Fas resistance and stabilization of β-catenin protein. Resistance to Fas-induced apoptosis may contribute to CML LSC persistence, and β-catenin activity increases during BC. In the current study, we directly tested the role of Fap1 in CML LSC persistence using in an in vivo murine model. In TKI-treated mice, we found that inhibiting Fap1, using a tripeptide or small molecule, prevented TKI resistance, BC and relapse after TKI discontinuation; all events observed with TKI alone. In addition, Fap1 inhibition increased Fas sensitivity and decreased β-catenin activity in CD34 + bone marrow cells from human subjects with CML. Therapeutic Fap1 inhibition may permit TKI discontinuation and delay in progression in CML.